Pathophysiological Ionotropic Glutamate Signalling in Neuroinflammatory Disease as a Therapeutic Target - Fairless, Richard; Bading, Hilmar; Diem, Ricarda (Frontiers in Neuroscience, 2021)
Glutamate signalling is an essential aspect of neuronal communication involving many different glutamate receptors, and underlies the processes of memory, learning and synaptic plasticity. Despite neuroinflammatory diseases covering a range of maladies with very different biological causes and pathophysiologies, a central role for dysfunctional glutamate signalling is becoming apparent. This is not just restricted to the well-described role of glutamate in mediating neurodegeneration, but also includes a myriad of other influences that glutamate can exert on the vasculature, as well as immune cell and glial regulation, reflecting the ability of neurons to communicate with these compartments in order to couple their activity with neuronal requirements. Here, we discuss the role of pathophysiological glutamate signalling in neuroinflammatory disease, using both multiple sclerosis and Alzheimer’s disease as examples, and how current steps are being made to harness our growing understanding of these processes in the development of neuroprotective strategies. This review focuses in particular on N-methyl-D-aspartate (NMDA) and 2-amino-3-(3-hydroxy-5-methylisooxazol-4-yl) proprionate (AMPA) type ionotropic glutamate receptors, although metabotropic, G-protein-coupled glutamate receptors may also contribute to neuroinflammatory processes. Given the indispensable roles of glutamate-gated ion channels in synaptic communication, means of pharmacologically distinguishing between physiological and pathophysiological actions of glutamate will be discussed that allow deleterious signalling to be inhibited whilst minimising the disturbance of essential neuronal function.